(untitled) (REVISTA NODO, 2026)
In this text I propose to delve into a philosophical and anthropological review of some phenomena that permeated the construction of dance in the prewar and postwar era, specifically under two socioculturals contexts: on one hand, from some aesthethic manifestations that emerged during the time of German expressionism and, on the other, from a brief approach to the roots of butoh dance in Japan. This critical review will allow us to understand the importance of the body experience in the construction of social sense, especially in a context of deep crisis.